Foot Self-Care in Type 2 Diabetes Mellitus: Effectiveness on Ankle-Brachial Index and Foot Sensitivity - Emyk Windartik; Dini Aprilia Putri; Vina Dwi Agustina (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Type 2 Diabetes Mellitus (T2DM) is associated with peripheral vascular disorders and diabetic neuropathy that may increase the risk of diabetic foot complications. Foot Self Care for Life is a comprehensive self-care intervention consisting of foot washing, drying, foot inspection, moisturizer application, nail care, and diabetic foot exercise. These interventions may improve peripheral circulation and sensory function. Determine the effectiveness of Foot Self Care for Life on Ankle Brachial Index (ABI) values and foot sensitivity among patients with Type 2 Diabetes Mellitus. Study employed a pre-experimental design using a one-group pretest-posttest approach. The study was conducted at RSUD Prof. dr. Soekandar from April 27 to May 23, 2026. A total of 40 patients with Type 2 Diabetes Mellitus were selected using accidental sampling. The intervention was administered for four weeks, seven times per week, with a duration of 45 minutes per session. ABI was measured using sphygmomanometer assessment, while foot sensitivity was assessed using a monofilament examination. Data was analyzed using Paired Sample t-Test and Wilcoxon Signed Rank Test. A significant increase in ABI values in the left foot (t=-7.530; p<0.001) and right foot (t=-8.651; p<0.001). Foot sensitivity also improved significantly in the left foot (Z=-5.657; p<0.001) and right foot (Z=-5.382; p<0.001). Foot Self Care for Life effectively improves peripheral circulation and foot sensitivity among patients with Type 2 Diabetes Mellitus. This intervention may be recommended as a non-pharmacological strategy to prevent diabetic foot complications. This study was approved by the Institutional Review Board (IRB) of Bina Sehat PPNI University Ethical Clearance Number: 175/KEP/UBS-PPNI/IV/2026.